The death of Randy Fitzsimmons [compact disc] (Disques Hives, 2023)
Undisputed icons of rock and roll The Hives are back, channeling the electrifying energy of the group's greatest hits with their first new album in over ten years. Their colossal new album, The Death Of Randy Fitzsimmons, reignites the band's lor in arresting fashion, exploring the disappearance of the band's mysterious sixth member Randy Fitzsimmons even leading them to dig up his grave. What they found inside the casket is what you can now hear on a record. Go fetch!